TABIAT VA INSON FAOLIYATIDA EKOLOGIK TOZA ENERGIYA MANBALARIDAN FOYDALANISHNING AHAMIYATI - Abdijaliev, S.K.; Allambergenova, D.A. (SCIENCE and SOCIETY, 2023)
This article provides information about the types of clean energy, its importance in nature and human activities, the benefits of using non-traditional methods to solve environmental problems.
Keywords: nature; ecology; energy; resource; fuel; wind